Security at risk : Malaysia and human trafficking - Jacquiline, Ebby Ramli (Universiti Malaysia Sarawak (UNIMAS), 2015)
Human trafficking is one of the fastest growing and spreading crimes in the world with global estimates ranging from 600,000 to 800,000 humans trafficked annually. Human trafficking is a complex crime in which it commonly involves organised crime syndicates. Human trafficking has affected many countries negatively and Malaysia is no exception. Being acknowledged as one of the transnational organised crime, human trafficking is capable of compromising the security and sovereignty of a country. Due to its strategic location and developing economy, Malaysia has been and continues to be a destination for many migrants with the initial intention to search for better economic opportunities but ended up as victims of human trafficking. Cross-border trafficking is one of the major concerns of Malaysia’s national security as Malaysia is a transit and destination, and to a lesser extent a source country for human trafficking. Long coastline borders complicate the issue of cross-border trafficking and allows the entries of migrants from neighbouring countries, especially from the economically poorer countries of Asia. The complexity of the issue is further compounded by corruptions. It is claimed that human trafficking encourages the practices of corruption. Consequently, it may also affect Malaysia’s relations with other countries. Cooperation between Malaysia and other countries, especially members of ASEAN specifically bilateral cooperation are made to tackle problem associated with human trafficking.